Nutritional Management of Critically Ill Trauma Patients in the Deployed Military Setting. Issue Volume 157:Issue (2011)Supplement 3 (1st September 2011) - Jansen, JO; Turner, S; Johnston, AMcD
Abstract : The role of nutritional support in critical illness is well established. This article reviews the nutritional management of military trauma patients in the deployed setting, which poses special challenges for the surgeon and intensivist. There is little direct evidence relating to the nutritional management of trauma patients in general, and military trauma patients in particular, but much of the evidence accrued in the civilian and non-trauma critical care setting can be extrapolated to military practice. There is strong consensus that feeding should be commenced as soon possible after injury. Enteral nutrition should be used in preference to parenteral nutrition whenever possible. If available, supplemental parenteral feeding can be considered if enteral delivery is insufficient. Gastrointestinal anastomoses and repairs, including those in the upper gastrointestinal tract, are not a contraindication to early enteral feeding. Intragastric delivery is more physiological and usually more convenient than post- pyloric feeding, and thus the preferred route for the initiation of nutritional support. Feeding gastrostomies or jejunostomies should not be used for short-term nutritional support. Enteral feeding of patients with an open abdomen does not delay closure and may reduce the incidence of pneumonia, and enteral nutrition should be continued for scheduled relook surgery not involving hollow viscera or airway. Glutamine supplementation may improve outcome in trauma patients, but fish-oil containing feeds, while showing some promise, should be reserved for subgroups of patients with ARDS.